PROFESIONALISME PUSTAKAWAN DALAM AJARAN HINDU DI ERA PERSAINGAN GLOBAL - I Gusti Ayu Ketut Yuni Masriastri; Elekmida Sinaga (Jurusan Dharma Acarya STAHN-TP Palangka Raya, 2019)
The concept of librarian professionalism and personality is a concept that has long been proclaimed and scheduled but, over time, the concept is as if forgotten and not glimpsed. If we may see the librarian is the main gate in providing services in the library. Librarians are also the driving engine (main engine) for the progress of a library. A librarian is required to be proficient at work, having good human resources (HR) and no less important is sounding good ethics and personality. In addition it must look attractive. A librarian has a good and attractive appearance reflected by his personality and good ethics. To have it all, a librarian must work from the heart, sincerely and sincerely devote himself. Personality and good ethics can not be easily formed but it requires effort and hard work and a sincere desire to achieve it. In the teachings of Hinduism the professionalism of a work (librarian) is in the books of Manawa Dharmasastra Sloka 100 and 161, the book Bhagawad Gita (Bh. G. XVI. 1) and (Bh. G. XVI. 2) and the book Sarasamuscaya sloka 300 and 302. In essence the above sloka teaches how a human being (librarian) behaves well in carrying out his work such as being honest, polite, not easily angry, gentle, not lying and working hard.